Updates on “cultural goodwill”: internationalization and diversity in Brazilian higher education - Michetti, Miqueli (FCL-UNESP Laboratório Editorial, 2019)
This article presents an analysis of the continuity and updates in the composition of the cultural capital in Brazil. From a case study based on participant observation carried out in a higher education institution in which medium-high and high fractions of Brazilian stratification predominate, the text shows how “capital of internationalization” and “capital of diversity” currently compose the search for cosmopolitanism as a distinctive element in symbolic disputes between groups and classes. Besides examining the modernity of the Bourdieusian notion of “cultural good will,” analyzing “international good will” and “reverse good will,” the article explores contradictions, tensions, and conflicts which emerge when the discourse of diversity, grounded in difference and inequality, is transformed into symbolic value among elite fractions.